Efficacy and Safety of Enoxaparin for Preventing Venous Thromboembolic Events following Urologic Laparoscopic Surgery. (2nd June 2013) - Nomura, Takeo; Takahashi, Mika; Iwasaki, Kazunori; Oribe, Tomoya; Shinohara, Mayuka; Fukuda, Yuko; Mizoguchi, Shinsuke; Sato, Fuminori; Mimata, Hiromitsu
Abstract : There is a paucity of definitive evidence that supports the use of enoxaparin to prevent venous thromboembolism (VTE) after urologic laparoscopic surgery. The purpose of this study was to evaluate the efficacy and safety of postoperative subcutaneous enoxaparin injection in patients who underwent urologic laparoscopic surgery. A total of 63 patients were evaluated from June 2010 to December 2012. All patients received postoperative prophylaxis with enoxaparin (2000 IU twice daily for 5 days). None of the patients treated with enoxaparin developed symptomatic VTE, but two cases (3.2%) of pulmonary embolism were noted before initial enoxaparin administration. Statistically significant differences were observed between the prothrombin time (PT) and activated partial thromboplastin time (APTT) values and D-dimer levels obtained at baseline and on day 7 after surgery; however, the PT and APTT values did not exceed the normal range. In addition, signs of any adverse events were not encountered in any of the patients treated with enoxaparin. The use of enoxaparin immediately after a surgery may confer valuable thromboprophylaxis benefits for urologic laparoscopic surgery.